Biopsy of sentinel lymph nodes after injection of methylene blue and lymphoscintigraphic guidance in 30 dogs with mast cell tumors. Issue 6 (6th July 2020) - Ferrari, Roberta; Chiti, Lavinia E.; Manfredi, Martina; Ravasio, Giuliano; De Zani, Donatella; Zani, Davide D.; Giudice, Chiara; Gambini, Matteo; Stefanello, Damiano
Abstract: Objective: To report the outcomes associated with sentinel lymph nodes (SLN) detection and extirpation guided by radionuclide and methylene blue injections in dogs with cutaneous and subcutaneous mast cell tumors (MCT). Study design: Clinical prospective cohort study. Animals: Thirty client‐owned dogs with MCT amenable to wide‐margin excision, without evidence of distant metastasis and abnormal regional lymph nodes (RLN). Methods: Technetium‐99 m and methylene blue were injected peritumorally. Dogs underwent preoperative γ‐camera scintigraphy and an intraoperative γ‐probe‐guided SLN extirpation. Outcomes included technical and surgical complications, number of SLN, SLN location respecting the expected RLN, and histopathology results. Results: Sentinel lymph node mapping was applied to 34 MCT in 30 dogs without any complication. Sentinel lymph nodes were not identified in three of 34 tumors, all with previous scar tissue. Sentinel lymph nodes did not correspond to expected RLN in 19 of 30 (63%) tumors. Histological examination confirmed an early or overt metastasis in 32 of 57 (56%) SLN extirpated. Conclusion: Sentinel lymph node mapping and biopsy with radionuclide and injection of methylene blue was associated with low morbidity and allowed detection of SLN in dogs with MCT at first presentation without scar tissue. Clinical significance: Incorporation of SLN mapping and extirpation allows for a personalized staging approach in dogs with MCT. The presence of scar tissue in dogs with recurrent tumors seems to be a limitation for SLN mapping with this technique.